2020
DOI: 10.1200/jco.2020.38.15_suppl.e13656
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs7372209 single nucleotide polymorphism in gene for miRNA-26a-1 with tumor localization and disease outcome in patients with colorectal cancer from Bulgaria.

Abstract: e13656 Background: A retrospective study was carried out to investigate the association of functional rs7372209 single nucleotide polymorphism (SNP) in the 5'- region of pri-miRNA- 26a1 gene with a risk of colorectal cancer (CRC) in a Bulgarian population, to evaluate its role as a potential prognostic or predictive biomarker for the disease and to studied its affection on the expression of miRNA-26a-1 in patients with CRC. Methods: 101 patients with colorectal metastatic disease and 90 healthy volunteers, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study observed worse clinical RFS of CRC patients in the II stage undergoing adjuvant chemo-radiotherapy who harbored T allele under dominant (CT + TT vs. CC) and overdominant (CT vs. CC + TT) genetic models [ 28 ]. In comparison, we found in a group of mCRC patients that TT genotype was significantly overrepresented in CRC patients with right-sided colon cancer than in patients with left-sided colon cancer and rectal cancer and associated with a longer mean OS than CT and CC genotypes [ 115 ].…”
Section: Snps In Genes For Mirnas Associated With Prognosis and Treatment Responsementioning
confidence: 99%
“…Another study observed worse clinical RFS of CRC patients in the II stage undergoing adjuvant chemo-radiotherapy who harbored T allele under dominant (CT + TT vs. CC) and overdominant (CT vs. CC + TT) genetic models [ 28 ]. In comparison, we found in a group of mCRC patients that TT genotype was significantly overrepresented in CRC patients with right-sided colon cancer than in patients with left-sided colon cancer and rectal cancer and associated with a longer mean OS than CT and CC genotypes [ 115 ].…”
Section: Snps In Genes For Mirnas Associated With Prognosis and Treatment Responsementioning
confidence: 99%